CREATIVE THINKING ABILITY OF STUDENTS WITH THEORIST AND PRAGMATIST LEARNING STYLES IN SOLVING NUMBER OPERATION PROBLEMS - Erina Ellen Rusmana; Ali Shodikin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
Creative thinking skills are essential in mathematics learning to address 21st-century challenges. This study aims to describe the creative thinking abilities of students with theorist and pragmatist learning styles in solving problems on number operations. The research employed a descriptive qualitative approach, with two subjects representing theorist and pragmatist learning styles, selected using purposive sampling from 27 seventh-grade students. The research instruments included the Learning Style Questionnaire (LSQ), problem-solving tests, and interview guidelines. Data were collected through questionnaires, tests, and interviews, then analyzed based on the indicators of fluency, flexibility, originality, and elaboration. The results revealed that students with a theorist learning style tend to produce structured and logical solutions, utilizing various approaches but showing limited innovation. Conversely, students with a pragmatist learning style demonstrated more practical and flexible approaches, along with originality through unique strategies, although their accuracy depended on precise assumptions. In conclusion, creative thinking abilities are influenced by students’ learning styles. Teachers are advised to provide exercises targeting all aspects of creative thinking to enhance the variation and quality of students' solutions.Kemampuan berpikir kreatif merupakan keterampilan penting dalam pembelajaran matematika untuk menghadapi tantangan abad ke-21. Penelitian ini bertujuan mendeskripsikan kemampuan berpikir kreatif siswa dengan gaya belajar teoris dan pragmatis dalam menyelesaikan masalah pada materi operasi bilangan. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan subjek dua siswa, masing-masing mewakili gaya belajar teoris dan pragmatis, yang dipilih melalui teknik purposive sampling dari 27 siswa kelas VII. Instrumen penelitian meliputi Learning Style Questionnaire (LSQ), tes pemecahan masalah, dan pedoman wawancara. Data dikumpulkan melalui metode angket, tes, dan wawancara, kemudian dianalisis berdasarkan indikator kelancaran, keluwesan, keorisinalan, dan elaborasi. Hasil penelitian menunjukkan bahwa siswa dengan gaya belajar teoris cenderung menghasilkan solusi yang terstruktur dan logis, menggunakan berbagai pendekatan, tetapi kurang inovatif. Sebaliknya, siswa dengan gaya belajar pragmatis lebih praktis dan fleksibel, serta mampu menunjukkan keorisinalan melalui strategi unik, meskipun masih terbatas pada keakuratan asumsi. Kesimpulannya, kemampuan berpikir kreatif dipengaruhi oleh gaya belajar siswa. Guru disarankan untuk memberikan latihan yang melatih seluruh aspek berpikir kreatif guna meningkatkan variasi dan kualitas solusi siswa.